Data and Inquiry Driving School Improvement: Recent Developments in England - Peter Earley; Sara Bubb (LED Edizioni Universitarie, 2014)
In this paper we draw upon recent developments in England to show how school leaders are using evidence and data for the purposes of school improvement and teachers are becoming more «research engaged» or research orientated. Particular interest is given to how schools are attempting to close the gap between the performance of children from different socio-economic backgrounds.  A policy initiative - the Pupil Premium - has led to school leaders looking closely at a range of improvement and intervention strategies, their effectiveness and the impact they have, especially on poor pupils.  We consider this and other related developments further, within an emerging self-improving system, and argue that school leaders are crucial for both data-driven improvement and for ensuring that school-based decision-making becomes evidence based or at least evidence informed. Research engagement does not just happen - it has to be led and managed. The vision is to change the culture of schooling so that practitioner inquiry and research engagement are important parts of teachers' professional practice. Inquiry-based school systems have been found to be a hallmark of high performing countries (Mourshed et al, 2010) and school leaders are key to the success of this system and cultural change. The paper concludes by considering what factors are important for this change to be realised.